Redundancy of IL-1 Isoform Signaling and Its Implications for Arterial Remodeling - Beltrami-Moreira, Marina (PLoS One, 2016)
AIMS: Mice deficient in IL-1 receptor 1 (hence unresponsive to both IL-1 isoforms α and β) have impaired expansive arterial remodeling due to diminished expression of matrix-degrading enzymes, especially MMP-3. Emergence of IL-1 as a target in cardiovascular disease prompted the investigation of the redundancy of IL-1α and IL-1β in the induction of MMP-3 and other matrix-remodeling enzymes in human cells. METHODS AND RESULTS: Human primary vascular smooth muscle cells (VSMCs) and carotid endarterectomy specimens were stimulated with equimolar concentrations of IL-1α or IL-1β and analyzed protease expression by immunoblot and ELISA. Either IL-1α or IL-1β increased the expression of pro-MMP-3 in VSMCs, facilitated VSMC migration through Matrigel, and induced MMP-3 production in specimens from atheromatous plaques. VSMCs also secreted MMP-1 and Cathepsin S (CatS) upon stimulation with IL-1α or IL-1β. IL-1 isoforms similarly increased MMP-1 and MMP-9 expression in carotid endarterectomy specimens. We examined the expression of MMP-3 and IL-1 isoforms by immunostaining of carotid atheromata, calculated the % positive areas, and tested associations by linear regression. MMP-3 colocalized with IL-1 isoforms in atheromata. MMP-3+ area in plaques positively associated with IL-1α+ (R2 = 0.61, P<0.001) and with IL-1β + areas (R2 = 0.68, P<0.001). MMP-3+ area within atheroma also associated with CD68+ area, but not with α-smooth muscle actin area. CONCLUSIONS: Either IL-1α or IL-1β can induce the expression of enzymes implicated in remodeling of the arterial extracellular matrix, and facilitate human VSMC migration in vitro. Human atheromata contain both IL-1 isoforms in association with immunoreactive MMP-3. This redundancy of IL-1 isoforms suggests that selective blocking of one IL-1 isoform should not impair expansive arterial remodeling, a finding with important clinical implications for therapeutic targeting of IL-1 in atherosclerosis.